Profil Pasien Leukemia Anak di RSUD Arifin Achmad Provinsi Riau Periode Tahun 2013-2014 - Fridayenti Fridayenti; Huriatul Masdar; Sherly Asriani (Fakultas Kedokteran Universitas Riau, 2015)
Leukemia is a malignancy of hematologic disease characterized by replacement of normal bone marrow by abnormalblood cells. Malignant neoplasm that most common in children. The aim of this study is to describe profiles ofleukemia in children in Arifin Achmad General Hospital period 2013-2014. This is a descriptive retrospective study.The data was used 48 medical records of child with leukemia. The highest frequency of child with leukemia wasfound in the age group of 5-9 years old (39.5%), the most frequent gender was male (62.5%) and mostly come fromPekanbaru (20.8%). Based on pheripheral blood smear, acute leukemia was found in 31.3 %, pancytopenia 22.9%,normocyitic anemia 18,8, hypocromic anemia 16.7% and neutropenia 2%. Based on morphologic of bone marrowALL was found in 79.2%, AML 10.4%, CML 8.3% and 2% analyzing was not included in leukemia. There are only15 patients having immunophenotyping assesment, 86.6% are ALL B-lineage, 6.7% are AML and 6.7% result wasnot sensitive to any leukemia marker.